2006
DOI: 10.1097/01.mpg.0000228120.44606.d6
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoiesis and Myocardial Energy Requirements Contribute to the Hypermetabolism of Childhood Sickle Cell Anemia

Abstract: Objectives-We hypothesized that an elevated hemoglobin synthesis rate (SynHb) and myocardial oxygen consumption (MVO 2 ) contribute to the excess protein and energy metabolism reported in children with sickle cell anemia.Patients and Methods-Twelve children (6-12 years old) with asymptomatic sickle cell and 9 healthy children matched for age and sex were studied. Measurements were whole-body protein turnover by [1-13 C]leucine, SynHb by [ 15 N]glycine, resting energy expenditure by indirect calorimetry and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 34 publications
2
42
0
2
Order By: Relevance
“…Resting energy expenditure was increased in several studies of children with SCD and is probably related to anemia, chronic inflammation, high cardiac output, and high protein turnover. [33][34][35] Interventions that decrease anemia and inflammation may have a beneficial effect on growth as well. HU has modest effects on the severity of hemolysis and anemia and may also decrease inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Resting energy expenditure was increased in several studies of children with SCD and is probably related to anemia, chronic inflammation, high cardiac output, and high protein turnover. [33][34][35] Interventions that decrease anemia and inflammation may have a beneficial effect on growth as well. HU has modest effects on the severity of hemolysis and anemia and may also decrease inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…6 Williams et al . reported that oral glutamate supplementation resulted in reduced REE among supplemented children with SCA, supporting our hypothesis of benefit from amino acid other than arginine, which is more widely reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…4 Sickle hemoglobin crystallizes during conditions of hypoxemia, leading to defective erythrocytes that are fragile and easily lysed. 5 The resulting chronic hemolysis and anemia are compensated, not only by exuberant erythropoiesis with increased catabolism and protein synthesis, 6 but also by chronic inflammation, secondary to ongoing vascular endothelial injury and recurrent vaso-occlusive events. 7,8 The net result is a hypermetabolic state, which causes increased utilization of protein/energy substrates, chronic nutritional deficiencies, and impaired growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Our study revealed a significant decrease in the BMI and waist circumference of the HbSS group when compared to the other Hb genotypes. Some of the reasons for this decreased growth and BMI are multifactorial with contributions from abnormal endocrine function [44], sub-optimal nutrition [45]; an increase in metabolism because of hyperactivity of the bone marrow and chronic inflammation [46] and hypogonadism [47]. Despite the limitations of our sample size, further research work using a community-based study with a larger sample size will make the study better.…”
Section: Discussionmentioning
confidence: 99%